Formation of HopQ1:14-3-3 complex in the host cytoplasm modulates nuclear import rate of Pseudomonas syringae effector in Nicotiana benthamiana cells - Rymaszewski, Wojciech; Giska, Fabian; Piechocki, Marcin A.; Zembek, Patrycja B.; Krzymowska, Magdalena (Frontiers in Plant Science, 2024)
HopQ1, a type three effector from Pseudomonas syringae upon phosphorylation coopts plant 14-3-3 proteins to control its stability and subcellular localization. Mass spectrometry of the cytoplasm-restricted effector revealed that HopQ1 already in this subcellular compartment undergoes phosphorylation at serine 51 within the canonical 14-3-3 binding motif and within the second putative 14-3-3 binding site, 24RTPSES29. Our analyses revealed that the stoichiometry of the HopQ1:14-3-3a complex is 1:2 indicating that both binding sites of HopQ1 are involved in the interaction. Notably, 24RTPSES29 comprises a putative nuclear translocation signal (NTS). Although a peptide containing NTS mediates nuclear import of a Cargo protein suggesting its role in the nuclear trafficking of HopQ1, a deletion of 25TPS27 does not change HopQ1 distribution. In contrast, elimination of 14-3-3 binding site, accelerates nuclear trafficking the effector.Collectively, we show that formation of the HopQ1:14-3-3 complex occurs in the host cytoplasm and slows down the effector translocation into the nucleus. These results provide a mechanism that maintains the proper nucleocytoplasmic partitioning of HopQ1, and at the same time is responsible for the relocation of 14-3-3s from the nucleus to cytoplasm in the presence of the effector.